The World War II : roots and causes - Eubank, Keith Hrsg (Problems in European civilization series, 1992)
Problem in interpretation: Another thirty years war? / P.M.H. Bell -- Hitler enigma: Policy for Germany / A. Hitler. Revisionist view / A.J.P. Taylor. Ideology of expansion / Norman Rich. Hitler's program / A. Hillgruber -- Aggression and appeasement: First victory / E.W. Bennett. Rhineland coup / J.T. Emmerson. Four year plan / A. Hitler. Strategy conference? / Hossbach memorandum. Hossbach memorandum evaluated / J. Wright and P. Stafford. Appeasement and appeasers / K. Eubank -- Czechoslovakia and Munich: Military implications of German aggression against Czechoslovakia / British Chiefs of Staff. Munich conference / G.L. Weinberg. War over Czechoslovakia? / W. Murray -- Intelligence muddle: British military intelligence / W.K. Wark. French military intelligence and the coming of war / A. Adamthwaite